Palaeolithic diet in the treatment of type 2 diabetes - Kuźmin, Laura (Journal of Medical Science, 2021)
The prevalence of type 2 diabetes has steadily increased over the past few decades. In the treatment of this disease, lifestyle modifications and dietary management are essential. There is evidence suggesting a beneficial impact of the Palaeolithic diet on monitoring glucose and insulin homeostasis; however, other studies have not confirmed these results. Therefore, further well-designed trials are necessary to demonstrate the health benefits of Palaeolithic nutrition in subjects with type 2 diabetes.